HuR (Human Antigen R) Regulates the Contraction of Vascular Smooth Muscle and Maintains Blood Pressure. Issue 4 (April 2020) - Liu, Shanshan; Jiang, Xiuxin; Lu, Hanlin; Xing, Mengdan; Qiao, Yanning; Zhang, Cheng; Zhang, Wencheng
Abstract : Objective: HuR (human antigen R)—an RNA-binding protein—is involved in regulating mRNA stability by binding adenylate-uridylate–rich elements. This study explores the role of HuR in the regulation of smooth muscle contraction and blood pressure. Approach and Results: Vascular HuR SMKO (smooth muscle–specific HuR knockout) mice were generated by crossbreeding HuR flox/flox mice with α-SMA (α-smooth muscle actin)-Cre mice. As compared with CTR (control) mice, HuR SMKO mice showed hypertension and cardiac hypertrophy. HuR levels were decreased in aortas from hypertensive patients and SHRs (spontaneously hypertensive rats), and overexpression of HuR could lower the blood pressure of SHRs. Contractile response to vasoconstrictors was increased in mesenteric artery segments isolated from HuR SMKO mice. The functional abnormalities in HuR SMKO mice were attributed to decreased mRNA and protein levels of RGS (regulator of G-protein signaling) protein(s) RGS2, RGS4, and RGS5, which resulted in increased intracellular calcium increase. Consistently, the degree of intracellular calcium ion increase in HuR-deficient smooth muscle cells was reduced by overexpression of RGS2, RGS4, or RGS5. Finally, administration of RGS2 and RGS5 reversed the elevated blood pressure in HuR SMKO mice. Conclusions: Our findings indicate that HuR regulates vascular smooth muscle contraction and maintains blood pressure by modulating RGS expression. Abstract : Supplemental Digital Content is available in the text.